(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The micro, small and medium businesses are being hit hardest by the coronavirus pandemic. The pandemic in India has mainly been disruptive, and India’s growth in the fourth quarter of the fiscal year 2020 went down to 3.1% as per the Ministry of Statistics.Covid-19 has taken the entire world into its grip and as a result people’s life and global economy have been disheveled. Covid-19 is a one of the giant disaster in the year 2020. The aim of this research paper is to study the effect on status of employment in MSMEs Sector and survival rate of MSMEs Sector in pre- post Covid-19 period and also to assess the major challenges faced by the MSMEs Sector in Covid-19 period in India. Lastly this study focused the different measures that are taken by the Government of India in MSME sectors to achieve the dream of Self- Reliant India or Atmanirbhar Bharat etc. After studying the devastating impact and various revival strategies, we found that business practices of Indian MSMEs will be totally changed. Digital practices, innovation, accessing of finance, focus on cash flows rather than profit will be essential after this covid -19 epidemic in India.